Direct transarterial embolization via the deep circumflex iliac artery for a type II endoleak using a novel Onyx™ mixture - Ghaly, Paul (J Surg Case Rep, 2020)
Internal iliac artery aneurysms (IIAA) can be associated with abdominal aortic aneurysms. We describe a technique of successful transarterial embolization using a mixture of Onyx™ formulations in a 72-year-old with previous open and endovascular aneurysm repairs of his abdominal aorta and a residual large left IIAA causing a Type II endoleak. We demonstrate that utilization of the deep circumflex iliac artery is a safe and viable alternate route to treating IIAA when direct access is not achievable.